Inspiratory muscle training improves breathing pattern during exercise in COPD patients. Issue 4 (25th February 2016) - Charususin, Noppawan; Gosselink, Rik; McConnell, Alison; Demeyer, Heleen; Topalovic, Marko; Decramer, Marc; Langer, Daniel
Dyspnoea is typically the main symptom limiting exercise capacity in patients with chronic obstructive pulmonary disease (COPD) [1–3]. Exertional dyspnoea has been linked to dynamic hyperinflation (DH), when lung expansion critically encroaches upon the inspiratory reserve volume (IRV) [4]. Consequently, patients develop a rapid and shallow breathing pattern, which is energetically opposite to the pattern required to minimise the work of breathing [5]. Furthermore, the restriction of tidal volume ( V T ) expansion has recently been linked to daily physical activity limitation [6]. The addition of IMT to a PR programme for selected COPD patients changes breathing pattern during exercise http://ow.ly/WWrFT